Highly sensitive visible to infrared MoTe2 photodetectors enhanced by the photogating effect. (26th September 2016) - Huang, Hai; Wang, Jianlu; Hu, Weida; Liao, Lei; Wang, Peng; Wang, Xudong; Gong, Fan; Chen, Yan; Wu, Guangjian; Luo, Wenjin; Shen, Hong; Lin, Tie; et al.
Abstract: Two-dimensional materials are promising candidates for electronic and optoelectronic applications. MoTe2 has an appropriate bandgap for both visible and infrared light photodetection. Here we fabricate a high-performance photodetector based on few-layer MoTe2 . Raman spectral properties have been studied for different thicknesses of MoTe2 . The photodetector based on few-layer MoTe2 exhibits broad spectral range photodetection (0.6–1.55 μ m) and a stable and fast photoresponse. The detectivity is calculated to be 3.1 × 10 9 cm Hz 1/2 W −1 for 637 nm light and 1.3 × 10 9 cm Hz 1/2 W −1 for 1060 nm light at a backgate voltage of 10 V. The mechanisms of photocurrent generation have been analyzed in detail, and it is considered that a photogating effect plays an important role in photodetection. The appreciable performance and detection over a broad spectral range make it a promising material for high-performance photodetectors.